Dynamics of Lymphocyte Populations during Trypanosoma cruzi Infection: From Thymocyte Depletion to Differential Cell Expansion/Contraction in Peripheral Lymphoid Organs - Alexandre Morrot; Juliana Barreto de Albuquerque; Luiz Ricardo Berbert; Carla Eponina de Carvalho Pinto; Juliana de Meis; Wilson Savino (Journal of Tropical Medicine)
The comprehension of the immune responses in infectious diseases is crucial for developing novel therapeutic strategies. Here, we review current findings on the dynamics of lymphocyte subpopulations following experimental acute infection by Trypanosoma cruzi, the causative agent of Chagas disease. In the thymus, although the negative selection process of the T-cell repertoire remains operational, there is a massive thymocyte depletion and abnormal release of immature CD4+CD8+ cells to peripheral lymphoid organs, where they acquire an activated phenotype similar to activated effector or memory T cells. These cells apparently bypassed the negative selection process, and some of them are potentially autoimmune. In infected animals, an atrophy of mesenteric lymph nodes is also observed, in contrast with the lymphocyte expansion in spleen and subcutaneous lymph nodes, illustrating a complex and organ specific dynamics of lymphocyte subpopulations. Accordingly, T- and B-cell activation is seen in subcutaneous lymph nodes and spleen, but not in mesenteric lymph nodes. Lastly, although the function of peripheral CD4+CD8+ T-cell population remains to be defined in vivo, their presence may contribute to the immunopathological events found in both murine and human Chagas disease.